Haliphthoros sabahensis sp. nov. isolated from mud crab Scylla tranquebarica eggs and larvae in Malaysia - Lee, Yih Nin; Hatai, K.; Kurata, O. (2017)
Mass mortality of eggs and larvae of the mud crab Scylla tranquebarica occurred at a hatchery in Sabah, Malaysia in June 2014. The mortality of the larvae reached nearly 100% within 5 days post-hatching. We isolated a pathogenic Peronosporomycetes (Oomycota) from the mud crab eggs and larvae using peptone-yeast-glucose-seawater (PYGS) agar, and then randomly selected the strain IPMB 1402 from the isolates for further study. We observed the formation of fragments inside the hyphae, a characteristic of Haliphthoros species. The strain morphologically most resembled Haliphthoros milfordensis, but comparisons of DNA sequences of the ITS1 region confirmed that the strain was not identical to that species. We classified the strain into a clade with Haliphthoros sp. group 2 (comprising strains NJM 0440, NJM 0449 and NJM 0535) after determining 97-100% intraspecific similarity. Based on distinctive morphological and molecular characteristics, the strain IPMB 1402 is here assigned to the genus Haliphthoros and designated Haliphthoros sabahensis sp. nov. Like other recognized species of Haliphthoros, it is an obligate marine fungus; growth was observed in pH 4-9, and optimum growth temperature was 25-30°C. The strain was experimentally pathogenic to nauplii of the brine shrimp Artemia salina.